Factors affecting onion market supply in Medebay Zana district, Tigray regional state, Northern Ethiopia - Teklebrhan Abrha (Cogent Food & Agriculture, 2020)
A number of challenges hampered the development of the onion sector along with the market in the Medebay Zana district, Tigray, Ethiopia. This study was initiated to analyze the determinants of the onion market supply by farm households in the study area. Both primary and secondary data were used for the study. Primary data were collected from 121 farm households selected randomly using a semi-structured questionnaire. About 12 wholesalers and 31 retailers engaged in onion trading were interviewed to explore the onion marketing channel in the study area. Results of the multiple regression model indicated that the amount of onion produced, access to extension service and market information positively and significantly predicted the quantity of onion supplied to the market. Hence, government, non-governmental organizations and other stockholders should play a vital role in addressing the constraints of onion production. Extension agents need to help onion farmers to improve onion production through improved farm management and conservation, as well as through improved varieties and integrated water, nutrient and pest management. An integrated agricultural marketing information system strengthens the linkage between onion producer and other value chain actors in the district and beyond.